2017
DOI: 10.1209/0295-5075/120/25001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cryogenic (hydrogen) and TESPEL (polystyrene) pellet particle deposition in a magnetically confined plasma

Abstract: A cryogenic pellet injector (PI) and tracer encapsulated solid pellet (TESPEL) injector system has been operated in combination on the stellarator TJ-II. This unique arrangement has been created by piggy-backing a TESPEL injector onto the backend of a pipe-gun–type PI. The combined injector provides a powerful new tool for comparing ablation and penetration of polystyrene TESPEL pellets and solid hydrogen pellets, as well as for contrasting subsequent pellet particle deposition and plasma perturbation under an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…For instance, the large outward drift acceleration experienced by ablated pellet material results in low fuelling efficiencies (<25%) for injections from the outer plasma edge of this device. Indeed, tracer injections with polystyrene (-C 8 H 8 -) based TESPELs have confirmed an inverse mass dependence of the acceleration [16]. Additional experiments have also revealed that enhanced pellet ablation in the plasma core due to fast-electron impacts can lead to higher fuelling efficiencies as the outward drift acceleration is disrupted in the initial drift phase [17].…”
Section: Plasma Fuelling and Impuritiesmentioning
confidence: 93%
“…For instance, the large outward drift acceleration experienced by ablated pellet material results in low fuelling efficiencies (<25%) for injections from the outer plasma edge of this device. Indeed, tracer injections with polystyrene (-C 8 H 8 -) based TESPELs have confirmed an inverse mass dependence of the acceleration [16]. Additional experiments have also revealed that enhanced pellet ablation in the plasma core due to fast-electron impacts can lead to higher fuelling efficiencies as the outward drift acceleration is disrupted in the initial drift phase [17].…”
Section: Plasma Fuelling and Impuritiesmentioning
confidence: 93%
“…Additional information on ablation and drift processes is obtained using a fast-frame CMOS camera equipped with a coherent double fibre bundle and interference filters. To date, TESPEL has been used in TJ-II to catalogue spectral line emissions (17 to 200 nm) of non-intrinsic impurities (Al, S, Ca, Sn, and W) [12], to investigate plasma termination and recovery [44], and to compare ablation and cloud drifting for different pellet types [45].…”
Section: Jinst 16 C12026mentioning
confidence: 99%
“…However, few systematic comparisons of these pellet types exist due to the limited number of devices equipped with both cryogenic and impurity PI systems. Moreover, for reference or comparison purposes, TESPEL pellets with no tracer are sometimes injected in TJ-II [61].…”
Section: Plasma Core Fuelling Pellet Physics and Modellingmentioning
confidence: 99%